Pengaruh Pretreatment Aerasi Kultur Tercampur Anaerob Terhadap Proses Aklimatisasi Pengolahan Limbah Cair Produksi Minyak Sawit - Pagattari, Hirda Nopma; Andrio, David; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Palm Oil Mill Effluent (POME) has potential for anaerobic treatment because it has COD concentration 50.000 – 70.000 mg/L. In this research, mixed cultures that we used is from cow dung. To increase concentration of bacteria on inoculum and decreased lag phase on anaerobic process, anaerobic mixed cultures should get seeding and acclimatized process. The bioreactor of seeding and acclimatization using circulating batch reactor, with volume 15 L and 5 L, respectively. Ratio wastewater to biomass bacteria was 70:30 (% v/v). This research used 3 variations of aeration time of mixed culture that is 0, 12, 24 and 36 hours. The parameter observed in this research was VSS and COD. Seeding process was doing in 5 days with final VSS on day-5 was 8.280 mg/L and total COD concentration was 36.454 mg/L. Acclimatization process was doing on three stages, 5 days each stage. The highest reduction of COD at the third stages of acclimatization was found within reactor with 24 hours of inoculum aeration pretreatment was 62% with 1.180 mg/L/day of increasing VSS.Keywords : POME, mixed culture, aeration pretreatment, seeding, acclimatization